Analisis Kesadarn Pegawai Negeri Sipil (PNS) dalam Menunaikan Zakat Profesi terhadap LAZIZNU - Rahmat Rahmat; Mohammad Ismail; Ismail Takdirullah; A. Muhyiddin Khotib (Journal of Economic and Islamic Research, 2023)
This study aims to analyze the implementation of Galis civil servants (PNS) in paying professional zakat to amil zakat institutions, infaq and how obstacles in implementing professional zakat to amil zakat institutions, infaq. The method used is qualitative descriptive with data collection techniques of observation, interviews and documentation then analyzed using the Mils and Hubberman model. From the results of the study showed that most civil servants in Galis sub-district have implemented zakat through a 2.5% salary deduction every month. there are several obstacle factors related to the awareness of civil servants in fulfilling professional zakat including, namely the lack of awareness of the obligation to pay professional zakat, lack of concern for underprivileged fellow Muslims who should really need financial assistance, and also their daily life dependents such as dependents to pay debts to the bank every month and other needs.